Leisure Activities in Political Perspective - T. V. Vdovenko; N. V. Gants (Управленческое консультирование)
The paper considers the fundamental notions and interpretations of leisure activities, their impact on the personality development, as well as their social and political significance.The authors provide a systematic sequential analysis of both historical and theoretical underlying principles of leisure activities, pointing out the diversity and complexity of the educational impact on an individual’s personality.The importance of the research into a person’s life outside working hours, namely leisure activities, could be accounted for firstly by its being a factor shaping a human’s mindset, being one of the survival prerequisites.Another factor consists in the importance of identifying the techniques designed to affect an individual, social groups, and the society as a whole. Political and social transformations of the lifestyle make us face new challenges of adjusting various strata of the society to the involvement in leisure activities, thus contributing to reducing social tension.The involvement of various age groups in the political and social areas of leisure activities enables the scholars to establish optimal techniques to develop and educate actors. Leisure activities built on expertise and meeting current community demands could become an important factor of shaping a proactive and creative personality.The paper considers ethnic, cultural, and political specificity as well as environmental features. Leisure activities enable a person to realize his/her potential and to express his/her attitudes. Leisure provides opportunities to extend one’s world outlook, to boost one’s inner self and enhance the involvement in politics.Building on the multi-disciplinary research, leisure can be described in various perspectives. It can be looked at in terms of philosophy, political studies, sociology, and pedagogy.The paper focuses on the perspectives of leisure activities development in the 21st century. Leisure is presented as a socio-political phenomenon empowering a person to exploit his/her potentials, and focusing on involving the young in the current political developments of a society.